Comparative Study of Two Laryngeal Mask Airways: Proseal Laryngeal Mask Airway and Supreme Laryngeal Mask Airway in Anesthetized Paralyzed Adults Undergoing Elective Surgery - Gill, Ravneet Kaur (Anesth Essays Res, 2017)
CONTEXT: Supraglottic airway devices can act as an alternative to endotracheal intubation in both normal and difficult airway. LMA Proseal (P-LMA) and LMA Supreme (S-LMA) alongwith acting as effective ventilating device, provide port for gastric drainage. AIM: The objective of this study was to compare the two devices for effective ventilation and complications. SETTING AND DESIGN: A prospective, randomized, single-blinded study was conducted in a tertiary care teaching hospital. Methods: 100 patients of ASA grade I–II undergoing elective surgery under general anaesthesia were included after ethical committee clearance and written consent. Patients were randomly allocated size 4 P-LMA (Group P) or S-LMA (Group S) (50 patients in each group). Insertion attempt, insertion time, oropharyngeal leak pressure (OLP) and complications were compared. RESULTS: There was no difference demographically. The first insertion attempts were successful in 92% with P-LMA and 96% with S-LMA. Insertion time was faster in S-LMA. The mean OLP was 24.04 cmH2O in Group P and 20.05 cmH2O in Group S. Complications were cough, mild blood staining. CONCLUSION: Both can act as an effective ventilatory devices. But where LMA Proseal provides a more effective glottic seal by having a greater OLP, single use LMA Supreme provides acceptable glottic seal with easier and faster insertion, therefore, it can be accepted as better alternative to LMA Proseal.